3(x-9+4x-1)-2(9-x)=-65

Simple and best practice solution for 3(x-9+4x-1)-2(9-x)=-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-9+4x-1)-2(9-x)=-65 equation:


Simplifying
3(x + -9 + 4x + -1) + -2(9 + -1x) = -65

Reorder the terms:
3(-9 + -1 + x + 4x) + -2(9 + -1x) = -65

Combine like terms: -9 + -1 = -10
3(-10 + x + 4x) + -2(9 + -1x) = -65

Combine like terms: x + 4x = 5x
3(-10 + 5x) + -2(9 + -1x) = -65
(-10 * 3 + 5x * 3) + -2(9 + -1x) = -65
(-30 + 15x) + -2(9 + -1x) = -65
-30 + 15x + (9 * -2 + -1x * -2) = -65
-30 + 15x + (-18 + 2x) = -65

Reorder the terms:
-30 + -18 + 15x + 2x = -65

Combine like terms: -30 + -18 = -48
-48 + 15x + 2x = -65

Combine like terms: 15x + 2x = 17x
-48 + 17x = -65

Solving
-48 + 17x = -65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + 17x = -65 + 48

Combine like terms: -48 + 48 = 0
0 + 17x = -65 + 48
17x = -65 + 48

Combine like terms: -65 + 48 = -17
17x = -17

Divide each side by '17'.
x = -1

Simplifying
x = -1

See similar equations:

| x-21=25 | | 5(x+3)=90 | | 2y-30+x=180 | | -4(y+9)=-3y-2 | | 5x^2=8-18x | | sin^22x+cos^2x=0 | | 3cot^2(2x)-1=0 | | -8+4y=32 | | -9r-7=110 | | 2(z-0.8)-5.8-1.3z= | | 120-2x=4x | | 3n(8n^2-2n+3)=0 | | 8x+16-7x=-4-13 | | -8m+4=60 | | xsquared-100=0 | | 7(9tk)=84 | | 8t+5=72 | | 2(-4x+8)+3(x-5)=-4 | | Bx-6y=18 | | 2x-4(x-3)=-6+2x+10 | | 18-C*3=9 | | 4n+12=56 | | X^2-15+2x=180 | | 7x-2y+3=0 | | 2sin^2x-5sinx-3=0 | | 8x-4=8(x-7) | | X+x+x=72 | | y=6x^3-72x^2+864x-3456 | | 4x^3-50x^2+150x=0 | | 26=2(w-5)+2w | | solvey=6x^3-72x^2+864x-3456 | | x-5.38=2.66 |

Equations solver categories